Microfluidic Electrochemical Desalination using a Permselective Membrane - Taleb, Haya Mohammad (2024)
A Master of Science thesis in Chemical Engineering by Haya Mohammad Taleb entitled, “Microfluidic Electrochemical Desalination using a Permselective Membrane”, submitted in December 2024. Thesis advisor is Dr. Naif Darwish. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).